2006
DOI: 10.1554/06-110.1
|View full text |Cite
|
Sign up to set email alerts
|

When Rensch Meets Bergmann: Does Sexual Size Dimorphism Change Systematically With Latitude?

Abstract: Bergmann's and Rensch's rules describe common large-scale patterns of body size variation, but their underlying causes remain elusive. Bergmann's rule states that organisms are larger at higher latitudes (or in colder climates). Rensch's rule states that male body size varies (or evolutionarily diverges) more than female body size among species, resulting in slopes greater than one when male size is regressed on female size. We use published studies of sex-specific latitudinal body size clines in vertebrates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
197
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(212 citation statements)
references
References 51 publications
8
197
4
3
Order By: Relevance
“…of Nottingham,Nottingham,, Dept of Zoology, Tel-Aviv Univ., Tel-Aviv, Israel. Research (Fairbairn 2007). For example, Cardillo (2002) found no latitudinal trend in SSD of birds, while Blanckenhorn et al (2006) found latitudinally structured variation in SSD for two-thirds of 96 species from a variety of taxa. However, these geographical patterns are not ubiquitous.…”
Section: Introductionmentioning
confidence: 98%
“…of Nottingham,Nottingham,, Dept of Zoology, Tel-Aviv Univ., Tel-Aviv, Israel. Research (Fairbairn 2007). For example, Cardillo (2002) found no latitudinal trend in SSD of birds, while Blanckenhorn et al (2006) found latitudinally structured variation in SSD for two-thirds of 96 species from a variety of taxa. However, these geographical patterns are not ubiquitous.…”
Section: Introductionmentioning
confidence: 98%
“…The observed tendency can be characterized in the following way: the sooner the frost-free period begins and the larger the number of warm days in a year is, the larger the E. ligea male wings are. It is obvious that the sooner the frost-free period comes, the longer the vegetation period is in general (allowing caterpillars to feed on average longer than in the regions with shorter summer) (Blanckenhorn et al, 2006). Unfortunately, we have female samples from only three studied habitats (Table 1), which does not allow us to fully estimate the character of their variability depending on analyzed climatic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Geographical variability of sizes (the length of fore and hind wing) is characterized by a cline consisting of a gradual increase in imago sizes in the direction from north to south (that is in general typical for monovoltine Lepidoptera) (Nylin and Svärd, 1991;Blanckenhorn et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals and other vertebrates, strong sexual selection faced by males is the mechanism most widely accepted to explain Rensch's rule in species with male-biased SSD (Abouheif and Fairbairn 1997;Dale et al 2007). However, which endothermic animals follow Rensch's rule remains unclear because opposite patterns have been found in taxa where females are the larger sex, exhibiting the converse of Rensch's rule (Blanckenhorn et al 2006;Webb and Freckleton 2007). In other taxa, neither Rensch's rule nor the converse of Rensch's rule is followed (Tubaro and Bertelli 2003;Liao et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another widespread pattern that describes body size variation is Rensch's rule, which states that SSD becomes more evident and male-biased when body size increases (Rensch 1950;Blanckenhorn et al 2006). In mammals and other vertebrates, strong sexual selection faced by males is the mechanism most widely accepted to explain Rensch's rule in species with male-biased SSD (Abouheif and Fairbairn 1997;Dale et al 2007).…”
Section: Introductionmentioning
confidence: 99%